Ancient European Synagogues in the Drawings by G. K. Lukomsky - Diodorovna, Ludmila D. (Actual Problems of Theory and History of Art, 2016)
The article is devoted to one of the areas of graphic creativity of the artist-architect and art historian, the purist of architectural antiques, George Crescentia Lukomsky (1884–1952), in the years of emigration. G. K. Lukomsky lived in exile for more than 30 years, but his creative work previous study by local and foreign historians has not covered all the aspects of his activities. Among these activities, there is a series of Jewish religious architecture drawings.In the 1920–30s, when he was in exile, the artist was seriously fascinated by the architectural forms of ancient synagogues. Visiting Volhynia, Galicia, Poland, and then Italy, France, Spain, Germany, Holland, England, and Portugal, the artist sketched more than 200 synagogues and was delighted with the originality of these remarkable temples. From 1934 to 1936, in the galleries of England, France and Portugal, there were a number of successful exhibitions of old European synagogues drawings. They were reflected in the émigré press and in the publications by G. K. Lukomsky himself, little known to our contemporaries.The article reveals poorly studied aspects of G. K. Lukomsky’s graphic and artistic heritage. Finally, the author makes a special tribute to the significant contribution to the study of religious Jewish architecture of Europe made by Lukomsky.
Keywords: drawing; G. K. Lukomsky; European synagogue